Inhibition of Endothelial Inflammatory Response by HT-C6, a Hydroxytyrosol Alkyl Ether Derivative - Ana Dácil Marrero; Laura Castilla; Manuel Bernal; Inmaculada Manrique; Joel D. Posligua-García; Federico Moya-Utrera; Cristina Porras-Alcalá; José Luis Espartero; Francisco Sarabia; Ana R. Quesada; Miguel Ángel Medina; Beatriz Martínez-Poveda (MDPI AG, 2023)
Hydroxytyrosol (HT) is a bioactive phenolic compound naturally present in olives and extra virgin olive oil (EVOO) which is described as an antioxidant, antitumoral and antiangiogenic molecule. Previous studies of semi-synthetic HT-derivatives presented the hydroxytyrosyl alkyl ether HT-C6 as one of the most potent derivatives studied in the context of antioxidant, anti-platelet and antiangiogenic assays, but its direct effect on inflammation was not reported. In this work, we use RT-qPCR measure of gene expression, protein analysis by Western-blot and immunofluorescence techniques, adhesion and migration functional assays and single-cell monitoring of reactive oxygen species (ROS) in order to explore in vitro the ability of HT-C6 to interfere in the inflammatory response of endothelial cells (ECs). Our results showed that HT-C6 strongly reduces the TNF-α-induced expression of vascular cell adhesion molecule 1 (VCAM1), intercellular cell adhesion molecule 1 (ICAM1), E-selectin (SELE), C-C motif chemokine ligand 2 and 5 (CCL2 and CCL5) in HUVECs, impairing the chemotactic and adhesion potential of these cells towards THP-1 monocytes in vitro. In this work, we define a mechanism of action underlying the anti-inflammatory effect of HT-C6, which involves the abrogation of nuclear factor kappa B (NF-κB) pathway activation in ECs. These results, together with the ability of HT-C6 to reduce ROS formation in ECs, point to this compound as a promising HT-derivative to be tested in the treatment of atherosclerosis.